DETERMINATION OF TRIFLURALIN AND CHLORIDAZON RESIDUES IN AGRICULTURAL LANDS IN ELAZIG PROVINCE - TUTARLI, A; CICI, M; CELIK, S (Selper Ltd, Publications Div, 1995)
In this study, operating parameters of the gas chromatograph are described for the determination of trifluralin and chloridazon in the soil. Average recoveries of these pesticides from previously-untreated soil were 85 % for trifluralin and 89 % for chloridazon fortified at 2 mg/40 g soil and 0.2 mg/40 g soil levels. Trifluralin and chloridazon were sprayed uniformly by aerial application on two small field plots (each 250 m(2)) containing agricultural land that had never been treated with pesticide. Soil samples collected from these field plots at certain time periods and depths were analysed by Gas Chromatography (GC). The results of analysed soil samples within a B-months period ranged from 6.0-0.2 mg/kg and 2.9-0.7 mg/kg for chloridazon, 7.1-1.5 mg/kg and 1.5-0.1 mg/kg for trifluralin at 0-5 cm and 15-20 cm depths, respectively. The residues of these pesticides were also investigated in agricultural lands in Elazig. The amount of trifluralin was found under the detection limits of GC. The other results indicate that residues of chloridazon are available and very important in the soil. In addition, the effects of volatilization and ultraviolet radiation (254 nm) were studied on the pure forms of trifluralin and chloridazon. The importance of each of these parameters on the disappearence rates of herbicides was determined separately by keeping herbicide at two different controlled temperatures (30 degrees C and room temperature) and exposing to UV light for 15 days.
Keywords: PESTICIDE; TRIFLURALIN; CHLORIDAZON; RESIDUE ANALYSIS